Isolation and Identification of Sensor and Resistance Bacteria to Lead and Mercury and Assess an Activity in Sensor and Removal: Ahmad M. Turki ,IA Assaffii , AH Mansur - Turki, Ahmad M. (The Iraqi Journal of Veterinary Medicine, 2011)
Study was conducted to isolate and diagnosis of bacterial which sensitiveand resistance for components of Hg and Pb, and the ability of these isolatefor resistance to remove high concentrations of Pb and Hg from componentsderived soil extract. Personalize Enterobacter cloacae 2w isolated filenameas isolated from soil extract wetthass to a concentration of 5 mg Pb/L and0.25 mg Hg/l. It also found that isolation resistance and treatable withordinary two Pseudomonas putida1N resisted concentration was 150 mg Pb/Land 3.5 mg Hg/l. And isolation resistance added massively vaccine Center6.2 Log cfu/ml of growth density 6.5 Log cfu/ml with a shot in the Center tofocus 90 mg Pb/L and remove 60% of It also has the same isolation ofgrowth-intensive 4.5 Log cfu/ml a concentration 3.5 mg Hg/L and remove68.9 percent during a incubation of 48 hours.